Human Skin Cancers Pathways, Mechanisms, Targets and Treatments - Blumenberg, Miroslav (IntechOpen, 2018)
Human skin cancers, the most common type of tumors, represent a significant health burden. The deadliest is unquestionably melanoma. Half of melanomas have an activating mutation in the BRAF gene, prompting development of novel drugs, vemurafenib and dabrafenib, specifically targeting mutated BRAF. Trametinib and cobimetinib, which block MEK, a BRAF effector protein, have been used in combination with BRAF inhibitors. A promising new melanoma treatment is immunotherapy, approach that boosts patient's own immune system to attack cancer. Pembrolizumab and nivolumab inhibit PD-1, whereas Ipilimumab targets CTLA-4, another immunity check point, to boost the immune response. Here we focus on pathways, mechanisms, targets and treatments of human skin cancers, with particular emphasis on the new developments in the research on melanomas.